Development of a core outcome set to use in the research and assessment of malignant bowel obstruction: protocol for the RAMBO study. Issue 6 (28th June 2020) - Baddeley, Elin; Bravington, Alison; Johnson, Miriam; Currow, David C; Murtagh, Fliss EM; Boland, Elaine; Obita, George; Nelson, Annmarie; Seddon, Kathy; Oliver, Alfred; Noble, Simon; Boland, Jason
Abstract : Introduction: Studies regarding the management of malignant bowel obstruction (MBO) report conflicting findings. This is partly due to different outcome measures being used to evaluate severity of MBO and the response to treatments. Furthermore, current outcome measures focus mainly on measurable physiological parameters which may not correlate strongly with patient-defined quality of life. The development of core outcome sets allows a consistent approach to evaluating clinical conditions taking into consideration patient, healthcare professional and researcher viewpoints. It follows an internationally recognised standard methodology. We present a protocol for the development of a core outcome set for Research and Assessment of MBO (RAMBO). Methods: RAMBO is a multicentre study, comprising of four phases: a systematic review to examine current scope of outcome measures associated with MBO (phase I). Interviews with patients, companions and healthcare professionals will explore priorities and preferences for care and outcomes (phase II). An expert panel meeting will collate the findings into a set of outcomes (phase III), refined by consensus through a Delphi survey with key stakeholders (phase IV). The final set of outcomes will be ratified at a consensus meeting. Each step will actively include patient partners. Thematic analysis and descriptive statistics will be used to analyse qualitative and quantitative data, respectively. Ethics and dissemination: Ethical approval was obtained (Wales REC 5, REF: 19/LO/1876). Study participants and relevant stakeholders will be updated with newsletters and a lay summary at the end of the study. Abstracts will be submitted to national and international conferences, result papers will be submitted to peer-reviewed, open access journals. Trial and PROSPERO registration numbers: Core Outcome Measures in Effectiveness Trials (1402); Systematic Literature Review (CRD42019150648); Rapid Review (CRD42020176393).